The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1177/1099800410385839
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Crossover Trial of Kangaroo Care to Reduce Biobehavioral Pain Responses in Preterm Infants: A Pilot Study

Abstract: Kangaroo care (KC), skin-to-skin contact between mother and infant, is a promising method for blunting pain responses. This crossover pilot tested KC effects on biobehavioral responses to heel stick in preterm infants (30-32 weeks' gestational age, 2-9 days old) measured by Premature Infant Pain Profile (PIPP) and salivary and serum cortisol. Mother-infant dyads were randomly assigned to KC heel stick (KCH) first or incubator heel stick (IH) first. Study 1 (80-min study, N = 18) tested the effect of 80 min of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
2
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(119 citation statements)
references
References 94 publications
2
107
2
8
Order By: Relevance
“…To evaluate the effects of massage on premature infants, Acolet et al (1993) found a decrease in plasma cortisol concentration, but this was not significant (41). Cong et al (2011) selected two groups of preterm neonates and investigated the effects of kangaroo care and heel needling. The first group received 80 minute and the second group received 30 minute of KMC.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the effects of massage on premature infants, Acolet et al (1993) found a decrease in plasma cortisol concentration, but this was not significant (41). Cong et al (2011) selected two groups of preterm neonates and investigated the effects of kangaroo care and heel needling. The first group received 80 minute and the second group received 30 minute of KMC.…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol affects the metabolism, cardiovascular system, and central nervous system (19) . Salivary cortisol has been used in studies to assess the effects of non-pharmacological interventions against pain in newborn infants, including sucrose, the kangaroo position, and developmental care (20)(21)(22) .…”
Section: Discussionmentioning
confidence: 99%
“…65 However, some investigators have reported decreased cortisol concentrations and decreased autonomic indicators of pain in preterm infants during SSC, suggestive of a physiologic benefit. 66,67 The effects of breastfeeding on pain response have also been investigated. A Cochrane systematic review published in 2012 found that breastfeeding during a heel lance or venipuncture was associated with significantly lower pain responses in term neonates (eg, smaller increases in heart rate and shorter crying time), compared with other nonpharmacologic interventions such as positioning, rocking, or maternal holding.…”
Section: Nonpharmacologic Treatment Strategiesmentioning
confidence: 99%